Analysis of Fundamental Factors Affecting Islamic Bank Share Prices in Indonesia - Nurmalia, Gustika; Ardana, Yudhistira (KnE Social Sciences, 2024)
While investing in the stock market can generate profits, it can also generate losses. Understanding the impact of certain important components on stock prices can help investors make more profitable investment decisions. The study investigated the key components that influenced the price of sharia bank Indonesian shares. Secondary data used for research. The information comes from monthly financial statements compiled from June 2018 to December 2020. The study looked at the impact of the shock and long-term response of each variable on the stock price using the Vector Error Correction Model (VECM). In the long run, PER and ROE variables have a positive effect on the stock price, but EPS has a negative effect. Unlike other variables, DER and PBV do not affect the stock price. The main factor is the EPS, which has a big and positive impact on the stock price in the short term. DER and PER have a very negative impact on the value of stocks. PBV has a negative but non-significant impact, while ROE has a positive but not significant impact. Keywords: Fundamental Factor, Stock Price, Vector Error Correction Model